Case report: ballotable abdominal mass in a child – Definitely renal in origin? - Guan Tatt Lim; Teh, Yong Guang; Ng, Chiak Yot; Hazlina Mohd Khalid; Firdaus Hayati (Elsevier Ltd, 2021)
Introduction and importance: The differential diagnosis of a paediatric abdominal mass can be extensive, as it potentially involves multiple organs including gastrointestinal, genitourinary, endocrine, and gynaecological systems. Hence, a systematic approach to history taking and physical examination is needed to clinch the diagnosis. Specifically, the approach for assessing, investigating, and managing a ballotable left hypochondrial mass in a child can be challenging. Case presentation: We report a 10-year-old Dusun girl presenting with left hypochondrial pain and noted a left hypochondrial mass on examination. This report highlights the role of clinical imaging during the pre-operative and post-operative phases. Clinical discussion: Ultrasound and CT imaging was useful in determining that the tumor originated from the tail of the pancreas. The presence of a definite capsule with internal solid-cystic components helped narrowed the differential diagnosis to solid pseudopapillary neoplasm (SPN) of the pancreas. MR liver was useful to rule out liver metastasis in this child. Intervention and outcome: The patient was scheduled for laparotomy and tumour excision at a regional paediatric centre. Successful excision of the tumor en-mass was performed and the child’s subsequent recovery was uneventful. Conclusion: Clinical imaging plays a critical role in the diagnosis and management of paediatric solid organ tumours. Other than renal origin, suspicion of pancreatic tail origin should be considered by clinicians when encountering a ballotable left abdominal mass